2021
DOI: 10.1097/upj.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Yearly Trends of Overactive Bladder Medication Usage

Abstract: Introduction: Anticholinergics are associated with cognitive side effects and dementia. Agents such as trospium, fesoterodine and darifenacin have been shown to be less likely to cross the blood-brain barrier. Furthermore, in 2012, mirabegron was approved by the U.S. Food and Drug Administration as the first beta-3 adrenoreceptor agonist to treat overactive bladder (OAB). This study aims to examine prescribing patterns of OAB medications in the United States over time. Methods:The 2013e2017 Medicare Part D Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
(48 reference statements)
2
11
0
Order By: Relevance
“…According to Medicare Part D national data set, oxybutynin and mirabegron were the most commonly prescribed OAB medications from 2014 to 2018. This is consistent with our findings because most case reports were from oxybutynin (27%) and mirabegron (35%) 7–9 . As expected, oxybutynin had the least proportion of NP ADEs given the majority of the administration is transdermal.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…According to Medicare Part D national data set, oxybutynin and mirabegron were the most commonly prescribed OAB medications from 2014 to 2018. This is consistent with our findings because most case reports were from oxybutynin (27%) and mirabegron (35%) 7–9 . As expected, oxybutynin had the least proportion of NP ADEs given the majority of the administration is transdermal.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with our findings because most case reports were from oxybutynin (27%) and mirabegron (35%). [7][8][9] As expected, oxybutynin had the least proportion of NP ADEs given the majority of the administration is transdermal. However, within NP subcategories, transdermal oxybutynin was associated with an increased risk of affect/mood disorder, agitation, and balance/movement disorder compared with all other OAB medications.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…They also showed that antimuscarinics (trospium, darifenacin, and fesoterodine), which produce lower cognitive side effects, were preferred for later stages of treatment. 34 In our study, among the antimuscarinic preferences in elderly OAB patients, trospium (URO 27.5%, GER 42.9%) and solifenacin (URO 27%, GER 20.6%) were the preferred drugs by URO and GER, while solifenacin (22%), oxybutynin (15.7%), and tolterodine (15.3%) were preferred by OB/GYNs. The quaternary molecular structure of trospium and noncrossing capability of blood-brain barrier of trospium might be the reason for choosing for this molecule.…”
Section: Discussionmentioning
confidence: 59%